Chemical and physical analysis of sesame oil by nuclear magnetic resonance spectroscopy and accelerated oxidation test - Nuamthanom, Anuttra; Phuriragpitikhon, Jenjira; Wattanakul, Titiporn (Bulletin of Applied Sciences, 2016)
In this work, we investigated the fatty acid composition of white sesame, black sesame, perilla (A and B) and artificail perilla (C) oils produced in Thailand using 1H-Nuclear magnetic resonance spectroscopy (1H-NMR) at 400 MHz. The composition of oleic (O), linoleic (L), linolenic (Ln), and saturated (S) is as follows: 41 % of O, 42 % of L and 17 % of S in black sesame oil ; 39 % of O, 43 % of L and 18 % of S in white sesame oil ; 14-15 % of O, 11-13 % of L, 54-55 % of Ln and 18-19 % of S perilla oil (A and B), and 14-15 % of O, 56 % of L and 22 % of S in artificail perilla (sample C). Based on the results, since perilla oil contained higher amount of Ln which is beleived to be benificial for health, its price is more expensive than balck and white sesame oils. In this study, we used the 1H-NMR signal from the methyl protons of Ln at the chemical shift of 0.95-0.99 ppm to distinguish between real and artificail perilla oil. Oxidative stability of all sesame was determined by using the Accelerated Oxidation Test tehnique which reveled that white sesame, black sesame, perilla (sample A and B) and artificail perilla (sample C) oil had oxidative stability values at 110 °C as 8.4h, oh, 1.4h, 1.6h and 3h respectively. These indicated that perilla oil had lower shelf life than white and black sesame oil. The artificail perilla oil had the oxidative stability value higher than real perilla but lower than white and black sesame oil, which was in accordance with data received from 1H-NMR spectroscopy.